Efficient Synthesis of Novel NK1 Receptor Antagonists: Selective 1,4-Addition of Grignard Reagents to 6-Chloronicotinic Acid Derivatives - Hoffmann-Emery, Fabienne; Hilpert, Hans; Scalone, Michelangelo; Waldmeier, Pius (Journal of organic chemistry, 2006)
A new efficient synthesis of two novel classes of NK1 receptor antagonists, among them befetupitant and netupitant, starting from 6-chloronicotinic acid is described. The introduction of the o-tolyl substituent at C(4) of the pyridine ring was achieved by a one-pot selective 1,4-Grignard addition/oxidation sequence to 6-chloronicotinic acid or a derivative of it. The scope of this addition/oxidation sequence was examined. It was also shown that the carboxylic function can be converted to a methyl amino group by a Hofmann rearrangement followed by reduction. Furthermore, a new high-yielding synthesis of 2-(3,5-bistrifluoromethylphenyl)-2-methyl propionic acid based on the carbonylation of the tertiary alcohol obtained by Grignard addition of 3,5-bis(trifluoromethyl)bromobenzene to acetone was established.